Predicting speech perception outcomes following cochlear implantation in adults with unilateral deafness or highly asymmetric hearing loss - Kitterick, Pádraig T.; Lucas, Laura (Taylor & Francis, 2016)
Unilateral deafness and highly-asymmetric hearing loss can impair listening abilities in everyday situations, create substantial audiological handicap, and reduce overall quality of life. Preliminary evidence from early-phase studies in adults suggests that cochlear implantation may be effective in reversing some of these detrimental effects. Patient-level data from existing studies was re-analysed to explore potential factors that may be predictive of improved speech perception scores following implantation. The results suggest that duration of deafness in the severe-to-profoundly deaf ear and hearing sensitivity in the better (non-implanted) ear may be relevant when seeking to identify those candidates who are likely to obtain benefit following cochlear implantation.